2020
DOI: 10.1021/acsaem.0c00036
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Enhanced Catalytic Activity of Fe-Doped LiCoPO4for the Oxygen Evolution Reaction

Abstract: Developing highly active and stable catalysts for the oxygen evolution reaction (OER) is of significant importance for numerous electrochemical energy conversion devices. Previous accomplishments have shown that LiCoPO 4 is a promising catalyst for OER activity; however, its activity and stability at high potential still need improvement to meet the requirements of practical applications, and further studies are needed for its catalytic mechanism. Here, we report a series of Fe-doped LiCoPO 4 materials that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…However, the continuous oxidative decomposition of electrolyte [ 11 , 12 ] and the unstable cathode electrolyte interface [ 13 , 14 ] under 5 V high voltage caused by Co 2+ /Co 3+ , resulting in rapid capacity degradation during cycling, severely hindering the application of LiCoPO 4 cathode material. In addition, the Li/Co antisite exchange during the cycling process [ 15 , 16 , 17 ] and low intrinsically ionic and electronic conductivity [ 18 , 19 , 20 ] must also be overcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the continuous oxidative decomposition of electrolyte [ 11 , 12 ] and the unstable cathode electrolyte interface [ 13 , 14 ] under 5 V high voltage caused by Co 2+ /Co 3+ , resulting in rapid capacity degradation during cycling, severely hindering the application of LiCoPO 4 cathode material. In addition, the Li/Co antisite exchange during the cycling process [ 15 , 16 , 17 ] and low intrinsically ionic and electronic conductivity [ 18 , 19 , 20 ] must also be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Lots of work have been undertaken to solve these problems, including decreasing the cathode particle size and controlling the morphology to shorten the Li-ion migration distance [ 21 , 22 , 23 , 24 ]; coating the cathode particle with stable materials [ 25 , 26 , 27 , 28 ] or conductive materials [ 29 , 30 , 31 , 32 , 33 ] to stabilize the interface and reduce the side reaction; partial substitution at Co site [ 20 , 34 , 35 , 36 , 37 ] to improve the intrinsic ionic and electronic conductivity [ 34 , 35 , 38 , 39 , 40 ]; and adding electrolyte additives to suppress the electrolyte decomposition [ 14 , 41 , 42 ]. Every method has some effect in improving LiCoPO 4 cathode performance.…”
Section: Introductionmentioning
confidence: 99%
“…The original electronic structures of the catalysts may be changed by metal doping so as to produce better catalytic properties. In this perspective, the Fe-doping can improve the OER activity dramatically . Qiu et al reported that the Fe-CoOOH/G nanohybrids acted as a catalyst for OER.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising olivine structures is LiCoPO 4 (LCP) as a cathode material due to its high redox potential of around 4.8 V, its high energy density, and its theoretical capacity of ~167 mAhg −1 [1][2][3]. Nevertheless, it undergoes a low electrochemical performance for many reasons, such as its low lithium-ion and electronic conductivity and its high voltage effect on the lifetime of the electrolyte (stability) [4,5].…”
Section: Introductionmentioning
confidence: 99%